Incidentally Diagnosed Alport Syndrome in a Patient with Drug-Induced Vasculitis. (10th April 2019) - Lai, D.; Dave, N.; Raghavan, R.
Abstract : A 53-year-old woman is admitted with a serum creatinine of 16 mg/dl. Seven months earlier, she was diagnosed with heart failure and started on several medications, including Hydralazine. Laboratory studies revealed the presence of dual Anti-Neutrophil Cytoplasmic Antibodies (anti-MPO and anti-PR3), anti-nuclear and anti-histone antibodies. The clinical diagnosis was Drug-Induced ANCA Vasculitis (DIAV). Kidney histology, however, did not reveal crescents, but showed characteristic features of Alport's syndrome.